ХАЛЫҚТЫ ДИЗИМГЕ АЛЫЎ МӘМЛЕКЕТЛИК СИЯСАТ ТИЙКАРЫ - Утепова, Г.Б. (FAN va JAMIYAT, 2023)
In this article, the purpose of population registration is to have accurate and detailed general and demographic information about the population. Forming and developing the economic lifestyle of each country, giving the right direction to various problems occurring in people's lives, re-examining the issue of personnel, making proposals to the legislative chamber and studying the population scientifically on a large scale.